KOMUNIKASI PESAN IKLAN TELEVISI ONLINE MARKETPLACE DENGAN ANALISA SEMIOTIKA - ADHI DHARMA SURIYANTO (Jurnal Komunikasi, 2017)
Online store companies, marketplace and e-commerce business actors in their growth generate competition among the perpetrators. In the competition, advertising on television becomes one way to be a winner. One version of a television advertisement made by bukalapak.com becomes an advertising communication with messages and meanings in it. The research method used is qualitative descriptive method. Data collection techniques in this study using documentation and literature study, as well as references related to research. The analytical technique used is semiotic analysis by Charles Sander Pierse